Consumption inequality and family labor supply - Richard Blundell; Luigi Pistaferri; Itay Saporta-Eksten (Institute for the Study of Labor (IZA), 2012)
In this paper we examine the link between wage inequality and consumption inequality using a life cycle model that incorporates household consumption and family labor supply decisions. We derive analytical expressions based on approximations for the dynamics of consumption, hours, and earnings of two earners in the presence of correlated wage shocks, non-separability and asset accumulation decisions. We show how the model can be estimated and identified using panel data for hours, earnings, assets and consumption. We focus on the importance of family labour supply as an insurance mechanism to wage shocks and find strong evidence of smoothing of male's and female's permanent shocks to wages. Once family labor supply, assets and taxes are properly accounted for, there is little evidence of additional insurance.
Keywords: J22; 330; consumption; labor supply; earnings; inequality; Verbraucherausgaben; Soziale Ungleichheit; Haushaltseinkommen; Lohnstruktur; Schock; Familienökonomik; Arbeitsangebot; Schätzung; USA